Design and implementation of smart guided glass for visually impaired people - Islam, Md. Tobibul; Rashid, Mohd Abdur; Ahmad, Mohiuddin; Kuwana, Anna; Kobayashi, Haruo (Institute of Advanced Engineering and Science, 2022)
The objective of this paper is to develop an innovative microprocessor-based sensible glass for those who are square measure visually impaired. Among all existing devices in the market, one can help blind people by giving a buzzer sound when detecting an object. There are no devices that can provide object, hole, and barrier information associated with distance, family member, and safety information in a single device. Our proposed guiding glass provides all that necessary information to the blind person’s ears as audio instructions. The proposed system relies on Raspberry pi three model B, Pi camera, and NEO-6M global positioning system (GPS) module. We use TensorFlow and faster region-based convolutional neural network (R-CNN) approach for detection of objects and recognition of family members of the blind man. This system provides voice information through headphones to the ears of the blind person, and facile the blind individual to gain independence and freedom within the indoor and outdoor atmosphere.